Potential for the processing of Brazilian fruits - A review of approaches based on the state diagram. (15th February 2022) - Sviech, Fernanda; Ubbink, Job; Prata, Ana Silvia
Abstract: Brazil has an extraordinary biodiversity that is reflected both in the enormous variety of native fruits and in the significant number of introduced exotic ones that are well adapted to the tropical climate. Only a very limited number of these fruits are however marketed at a large scale. While so-called "non-conventional fruits" are often marketed locally, they are not used by the wider food industry because of their high perishability in fresh state. This renders them unsuitable for long distribution chains. These fruits may be converted into shelf-stable products that could generate significant added value by processing them into more stable forms. Knowledge of the phase behavior of fruits is critically important in the optimization of the process conditions of operations such as freezing, concentrating, and drying, including spray drying, drum drying, infrared drying and freeze drying. These properties are furthermore important for determining the storage conditions of fruit-based products. Our review compiles information on the composition and phase transitions (specifically the ice melting line and the water-content dependence of the glass transition) of a wide range of tropical fruits and analyzes these in the context of the state diagram of food systems. The use of these state diagrams in process optimization, product development and shelf-life analysis is furthermore discussed. By providing the first review of the phase behavior of diverse tropical fruits, we aim to facilitate their use in a wide range of food products and thereby stimulate the regional development of the generally poor regions in Brazil that grow these non-conventional fruits. Highlights: The large Brazilian biodiversity includes a wide variety of nonconventional fruits Nonconventional fruits have huge potential but are hardly used by the food industry Thermal processing may be used to develop shelf-stable fruit-based foods Knowledge of the phase transitions of fruits allows establishing process conditions This review reports on phase transitions and state diagrams of tropical fruits